The effect of cereal type and α-tocopherol supplementation on selective quality and processability parameters of milk from late lactation grazing dairy cows. Issue 1 (17th February 2021) - McKay, Zoe C.; O'Sullivan, Michael; Lynch, Mary B.; Mulligan, Finbar J.; Ma, Lu; Rajauria, Gaurav; Pierce, Karina M.
Abstract: This research communication addressed the hypothesis that late lactation cows offered an oat-grain-based supplement or a high level of α-TOC supplementation at pasture would have improved milk composition and processability. Over a grazing period of 49 d, 48 Holstein Friesian dairy cows were randomly assigned to one of four dietary treatments. The dietary treatments were: control, pasture only (CTRL ), pasture + 2.65 kg DM barley-based concentrate + 350 IU α-TOC/kg (BARLO ), pasture + 2.65 kg DM oat-based concentrate + 350 IU α-TOC/kg (OATLO ) and pasture + 2.65 kg DM oat-based concentrate + 1050 IU α-TOC/kg (OATHI ). Within this randomised complete block design experiment cows were blocked on days in milk (DIM) and balanced for parity, milk yield and composition. Rennet coagulation time (RCT) was reduced in milk from cows offered OATHI compared to CTRL cows and OATLO. Concentration of conjugated linoleic acid (CLA) was increased by OATHI compared to OATLO and in OATLO compared to CTRL. Supplementation with OATHI reduced individual saturated fatty acids (SFAs) in milk compared to OATLO. In conclusion, supplementing grazing dairy cows with an oat-based supplement improved total milk CLA concentration compared to pasture only. Offering a high level of α-TOC (2931 IU/d) to dairy cows reduced RCT, individual SFA and increased total CLA concentration of milk compared to a lower α-TOC level (738 IU α-TOC/d).